Effects of teaching practices on life satisfaction and test scores: evidence from the Program for International Student Assessment (PISA) - Stefano Bartolini; Kelsey J. O'Connor (Global Labor Organization (GLO), 2022)
Schools are ripe for policy intervention. We demonstrate that implementing different teaching practices is effective, finding a greater prevalence of group discussion used in schools positively affects students' life satisfaction and noncognitive skills but has no impact on test scores. The benefits do not apply to girls, however, unless they attend all-girl schools. These findings are based on a sample from the 2015 PISA which includes more than 35 thousand students from approximately 1500 schools in 14 countries or regions. We perform regressions of student life satisfaction on the prevalence of group discussion and lecturing used in their school, including a battery of individual, teacher, and school controls, as well as random intercepts by school. For robustness we use instrumental variables and methods to account for school-selection. The average impact of group discussion is not small – a one standard deviation leads to an increase in life satisfaction that is about one-half of the negative association with grade repetition. On the other hand, more or less lecturing does not affect life satisfaction, noncognitive skills, nor test scores. We conclude that teaching practices – group discussion – can be used to improve student life satisfaction, thereby likely positively affecting future economic outcomes and well-being.
Keywords: I21; I31; J24; 330; subjective well-being; teaching; teaching practices; non-cognitive skills; education; PISA; participatory teaching; vertical teaching; horizontal teaching